Memory-Modulation: Self-Improvement or Self-Depletion? - Lavazza, Andrea (Frontiers in Psychology, 2018)
Autobiographical memory is fundamental to the process of self-construction. Therefore, the possibility of modifying autobiographical memories, in particular with memory-modulation and memory-erasing, is a very important topic both from the theoretical and from the practical point of view. The aim of this paper is to illustrate the state of the art of some of the most promising areas of memory-modulation and memory-erasing, considering how they can affect the self and the overall balance of the "self and autobiographical memory" system. Indeed, different conceptualizations of the self and of personal identity in relation to autobiographical memory are what makes memory-modulation and memory-erasing more or less desirable. Because of the current limitations (both practical and ethical) to interventions on memory, I can only sketch some hypotheses. However, it can be argued that the choice to mitigate painful memories (or edit memories for other reasons) is somehow problematic, from an ethical point of view, according to some of the theories of the self and personal identity in relation to autobiographical memory, in particular for the so-called narrative theories of personal identity, chosen here as the main case of study. Other conceptualizations of the "self and autobiographical memory" system, namely the constructivist theories, do not have this sort of critical concerns. However, many theories rely on normative (and not empirical) conceptions of the self: for them, the actions aimed at mitigating or removing specific (negative) memories can be seen either as an improvement or as a depletion or impairment of the self.